Pengendalian Tekanan Darah dengan Black Garlic Varian Bawang Lanang pada Pasien Hipertensi - Ika Cahyaningrum; Errick Endra Cita (Universitas Baiturrahim, 2022)
Cardiovascular disease is a major health problem in the world. Hypertension is one of the most common cardiovascular diseases. Efforts to control and treat hypertension are very important so as not to cause complications. Hypertension control can be done with pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies is black garlic therapy with solo garlic variant. The type of research used is pre experimental with a one-group pretest and post-test design. Researchers analyzed the respondents' blood pressure before and after being given black garlic variant solo garlic therapy for 14 days. The research was carried out in the working area of the Gedangan Village Health Center, Malang Regency from March to June 2022. The population in this study were patients with hypertension in the working area of the Gedangan Health Center. The sampling technique used consecutive sampling with a total sampling of 20 samples. Analysis of the data used by using the paired t test. The results showed that there were differences in blood pressure values after consuming black garlic variants of garlic (systole -value 0.000, diastole -value 0.014). The hope is that the public can use non-pharmacological black garlic therapy, especially the solo garlick variant, as a complementary therapy in controlling blood pressure.